Stylistic Analysis of Edgar Allan Poes The Bells - Suparlan, Suparlan; Mul, Muliadi; Masyudin, Masyudin (Universitas Malikussaleh, 2019)
The element that makes the poem beautiful is a figure of speech. There are many types of figures of speech, for instance, metaphor, personification, irony, alliteration, onomatopoeia, and assonance. The researcher chooses Edgar Allan Poes The Bells to identify because the poem The Bells has not many often identified by using figures of speech. This research aimed to identify figures of speech and to find out the possible message that Edgar Allan Poe tries to convey in the poem. This research used qualitative and quantitative methods. The data and source of data took from Edgar Allan Poes The Bells. This poem has (29%) figures of speech is Metaphor, (27%) is Alliteration, (22%) Onomatopoeia, (11%) is Assonance, (9%) is Personification and (2%) is Irony. But only some figures of speech become the power in this poem. For instance, in researcher result, the power of figures of speech in the poem The Bells is Metaphor and Alliteration.